Review and Analysis of the Colombian Foreign Language Bilingualism Policies and Plans - Mary Mily Gómez Sará (HOW, 2017)
This article reviews the background of the foreign language bilingualism in Colombia, as well as the Colombian bilingualism plans and the policy launched between 2004 and 2016. Then, these plans and policy are analyzed taking into account the most common criticisms from the academic community. In this sense, aspects such as the lack of continuity, emphasis on employability, misconceptions of bilingualism, privileged position of English, adoption of the Common European Framework of Reference, English instruction as a way of business, and omission of teachers’ voices are analyzed.